HIV/AIDS in China : Beyond the Numbers - Wu, Zunyou (Public Health in China, 2017)
This book presents the history of HIV/AIDS in China, which over the last three decades has been a gripping tale of exclusion and fear, and then, by turns, of involuntary tragedy, cautious experimentation and finally vigorous response. It discusses the occurrence, development and epidemic studies and also introduces China's policies and measures to conquer this epidemic, offering readers valuable insights into China's approach to prevention in this field. Dr. Zunyou Wu is the Director of the National Center for AIDS/STD Control and Prevention, Chinese Center for Disease Control, Beijing, China.